Indigenous peoples’ political transnationalism: activism and the internationalisation of demands - Karla Nahuelpan Sánchez (Revista CIDOB d'Afers Internacionals, 2023)
This paper applies a historical, cultural and social perspective to analyse the political transnationalism of indigenous peoples. Using key concepts like indigenous movements and transnational defence networks, alongside desk study and analysis of indigenous organisations’ goals and programmes, this paper proposes a classification and definition of three types of indigenous political transnationalism: migratory, institutional and relating to transnational peoples. Examples are given for each, including indigenous organisations from America, Africa, Asia and international organizations, with the aim of revealing the complexity and importance of transnationalism as a fundamental factor in the indigenous protests of the last decades.